Agency Relationships in Family Firms: Theory and Evidence - Schulze, William S.; Lubatkin, Michael H.; Dino, Richard N.; Buchholtz, Ann K. (Organization Science, 2001)
Does owner management necessarily eliminate the agency costs of ownership? Drawing on agency literature and on the economic theory of the household, we argue that private ownership and owner management expose privately held, owner-managed firms to agency threats ignored by Jensen’s and Meckling’s (1976) agency model. Private ownership and owner management not only reduce the effectiveness of external control mechanisms, they also expose firms to a “self-control” problem created by incentives that cause owners to take actions which “harm themselves as well as those around them” (Jensen 1994, p. 43). Thus, shareholders have incentive to invest resources in curbing both managerial and owner opportunism. We extend this thesis to the domain of the family firm. After developing hypotheses which describe how family dynamics and, specifically, altruism, exacerbate agency problems experienced by these privately held, owner-managed firms, we use data obtained from a large-scale survey of family businesses to field test our hypotheses and find evidence which suggests support for our proposed theory. Finally, we discuss the implications of our theory for research on family and other types of privately held, owner-managed firms.